(untitled) (Journal of the College of Basic Education, 2023)
This paper examines the possibility of inserting linguistic elements in unusual positions. The outcome of such insertion has come to be known as a discontinuous structure. Learners of English as a foreign language are warned against the use of such structures in their speech or writing. However, in several cases the insertion of a word or a clause within a constituent or between constituents becomes obligatory or stylistically preferable. One striking example is the use of adverbials between the main verb of a sentence and its direct object when the object of the sentence is long or heavy.